Regulatory role of the START lipid/sterol binding domain in homeodomain transcription factors from plants - Khosla, Aashima (Kansas State University, 2015)
Class IV homeodomain leucine-zipper transcription factors (HD-Zip TFs) are master regulators of cell-type differentiation in the plant epidermis. These transcription factors contain a putative START (STeroidogenic Acute Regulatory (StAR)-related lipid Transfer) lipid/sterolbinding domain that is hypothesized to link metabolism to gene expression in plant development. This study is focused on two class IV family members that serve as models in many of the experiments: GLABRA2 (GL2) is a key regulator of differentiation in hair cells called trichomes as well as other epidermal cell types in various plant tissues. The second member addressed in this study is PROTODERMAL FACTOR2 (PDF2), which plays a crucial role in epidermal cell specification in shoots. A leading hypothesis is that the START domain, by binding a ligand, controls transcription factor function, analogously to nuclear receptors from mammals. Domain swap experiments indicated that the START domain from both plants and mammals is a conserved ligand-binding motif that is required for transcription factor activity. To further address its function in ligand binding, mutational analysis of the START domain of GL2 was performed. Several of the mutations remove charged residues in the predicted ligand-binding pocket and resulted in loss-of-function phenotypes, suggesting that ligand binding is critical for HD-Zip TF activity. Chromatin immunoprecipitation–based sequencing (ChIP-seq) revealed that the START domain is dispensable for transcription factor binding to DNA. Using a high throughput thermal shift assay to screen a library of pure natural compounds, specific secondary metabolites were identified as putative START domain ligands for PDF2. Experiments in both yeast and N. benthamiana demonstrated that the START domain is required for homodimerization of GL2 through its Zip domain. It was also found that the START domains physically interact with RHAMNOSE SYNTHASE I (RHM1). Further, this work provided evidence for a previously elusive redundancy between GL2 and another class IV HD-Zip TF, and unveils a positive feedback loop in the maintenance of the GL2 activity during trichome differentiation. Taken together, these findings support the premise that START domains are central players in metabolic regulatory networks that can modulate transcription factor activity by binding ligands and mediating protein-protein interactions.
Keywords: Lipids; Transcription factors; Arabidopsis